Probing the ionic liquid/semiconductor interfaces over macroscopic distances using X-ray photoelectron spectroscopy. (1st October 2019) - Foelske, Annette; Sauer, Markus
Abstract: In this study we investigate how electronic properties of buried semiconductor/ionic liquid interfaces may influence on charging effects observed by X-ray photoelectron spectroscopy (XPS). Droplets of the ionic liquid 1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl)imide ([EMIM][Tf2 N]) were deposited on silicon and germanium semiconductor surfaces with different doping states. Core level spectra were recorded from the ionic liquid/ultra-high vacuum interface with and without irradiation of the droplets using low energy electrons from a flood gun. Changing electron intensity results in shifts of the binding energy of all XPS signals to lower values. Magnitude of shifts is found to directly depend on the intensity of the electron beam and to correlate with the nominal resistivity of the substrates. The observations are qualitatively explained by flood gun induced changes of the electronic properties of the [EMIM][Tf2 N]/substrate interface and suggested to refer to space charge layer effects.